1999
DOI: 10.1038/sj.bjc.6690836
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of a residential radon remediation programme in the United Kingdom

Abstract: As residential radon programmes of identification and remediation have proceeded, so questions have been raised about their costs and benefits. This study presents a generalizable model for estimating the cost-effectiveness of a radon mitigation programme using the methodological framework now considered appropriate in the economic evaluation of health interventions. Its use will help to inform future discussion of radon remediation and lung cancer prevention programmes. Data from Northamptonshire were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…With 10% of householders organising remediation the Annualised Cost per annual lung cancer saved in Northamptonshire was £558 940 at a discount rate of 10%, which is similar to the value of £671 000 NRPB dental for the NHS workplace and therefore still cost-effective when compared to the NRPB programme to reduce patient dose from dental X-Rays. Recently, Kennedy et al (1999) have studied this series and shown that the cost per life year gained is similar to other health interventions, such as the national breast screening programme, which are considered by a range of agencies to be worthwhile. From Table 3, 10% of the existing housing having radon above the Action Level translates to a total of 417 houses, so this paper presents results for approximately 17Ð5% of these.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With 10% of householders organising remediation the Annualised Cost per annual lung cancer saved in Northamptonshire was £558 940 at a discount rate of 10%, which is similar to the value of £671 000 NRPB dental for the NHS workplace and therefore still cost-effective when compared to the NRPB programme to reduce patient dose from dental X-Rays. Recently, Kennedy et al (1999) have studied this series and shown that the cost per life year gained is similar to other health interventions, such as the national breast screening programme, which are considered by a range of agencies to be worthwhile. From Table 3, 10% of the existing housing having radon above the Action Level translates to a total of 417 houses, so this paper presents results for approximately 17Ð5% of these.…”
Section: Discussionmentioning
confidence: 97%
“…Even so, a costeffectiveness analysis of the current domestic remediation programme in Northamptonshire showed that the societal cost effectiveness per life year gained was of the same order as other accepted health interventions (Kennedy et al, 1999). This paper reviews the relative effectiveness of remediation programmes in both existing and new houses in Northamptonshire, which has a range of radon levels typical of any affected area.…”
Section: Introductionmentioning
confidence: 98%
“…The first of these corresponds with the latest advice offered by [26], who recommend applying a discount rate of 3% for projects that last beyond 30 years, as is assumed will be the case for the remediation programmes. Figures based on the higher rate are also reported to allow comparison with previously published studies, such as [18,25], where a rate of 6% was used in line with the guidelines in existence at the time those studies were conducted. The effect of using a lower discount rate, it will be seen in Section 4, is to reduce the cost per life-year gained for radon remediation.…”
Section: Methodsmentioning
confidence: 94%
“…[25] suggest that in Northamptonshire every lung cancer averted produces 13.51 additional life-years and it is this value which is used to estimate the total life-years gained from the remediation programme in the PCTs. In the absence of data on the ages of those remediating, these life-years gained are, following [25], assumed to be spread equally across a 40-year period and are discounted to present values. As the cost of obtaining these additional life-years is that of remediation, it is then a simple matter to determine the cost per life-year gained.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has studied radon extensively in Northamptonshire, considering hospitals [8,9], workplaces [10], schools [11] and domestic properties [12][13][14][15][16][17]. The underlying theme of each study was the assessment of the health benefits and the costs of comprehensive radon remediation programmes in the different classes of properties, and whether such programmes could be justified.…”
Section: Introductionmentioning
confidence: 99%